2015
DOI: 10.1177/1524839915570632
|View full text |Cite
|
Sign up to set email alerts
|

Latino Community Health Workers and the Promotion of Sexual and Reproductive Health

Abstract: Community health worker (CHW) programs have existed for over 50 years across the world. However, only recently has research evidence documented their effectiveness. Research is still needed to identify issues related to implementation and sustainability of CHW programs. This article explores the role and challenges of U.S. Latino CHWs trained to deliver a comprehensive sexual and reproductive health educational intervention to Latino families. We conducted a semistructured interview with a purposive convenienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Our results suggest that promotores’ work is indeed complex, in line with findings from prior research on the nature of work done by CHWs serving Latino communities (e.g., Lechuga et al, 2015; Seth, Isbell, Atwood, & Ray, 2015). The job analysis revealed that important duties of promotores involved communication, documentation, classroom facilitation, community outreach, patient referrals, teaching preparation, professional development, professionalism, and a variety of soft skills.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results suggest that promotores’ work is indeed complex, in line with findings from prior research on the nature of work done by CHWs serving Latino communities (e.g., Lechuga et al, 2015; Seth, Isbell, Atwood, & Ray, 2015). The job analysis revealed that important duties of promotores involved communication, documentation, classroom facilitation, community outreach, patient referrals, teaching preparation, professional development, professionalism, and a variety of soft skills.…”
Section: Discussionsupporting
confidence: 89%
“…Understanding and defining the roles of CHWs is critical for programs that employ them. To this end, a recent study by Lechuga, Garcia, Owczarzak, Barker, and Benson (2015) sought to shed light on the important roles and characteristics of CHWs promoting sexual and reproductive health in Wisconsin. The research and practice team used qualitative interviews to reach their goals, identifying the varied roles (real and expected) of CHWs, as well as challenges faced by workers in the field as a result of these role ambiguities.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, even as the resident children of undocumented immigrants are eligible for public health benefits through the Children’s Health Insurance Program, prior research demonstrates that these children have significantly fewer medical appointments and emergency room visits than the children of citizens, highlighting how the barriers faced by immigrant parents can affect their children [26]. While a lack of insurance presents an important barrier to accessing health care for Hispanic immigrants, prior research notes that access issues can be exacerbated by other barriers including the cost of care, transportation, the inability to take time away from work, child care, limited knowledge, language, gender, ethnicity, documentation status, and fear [2731].…”
Section: Introductionmentioning
confidence: 99%
“…While CHWs have many different job titles and roles as health promotors, community health advocates, health navigators, and more, all CHWs are public health practitioners unified in their efforts to connect with the populations they serve, often through shared experience and cultural understanding [3136]. Whether they work in the public, private, non-profit, or academic sectors, or just help as volunteers, their numbers are growing.…”
Section: Introductionmentioning
confidence: 99%
“…Although titles vary—CHWs, promotoras , lay health advisers—CHWs typically are individuals without formal education who are trained to promote health and advocate for change in their communities ( Carrasquillo et al, 2014 ). Increasingly, there is widespread involvement of CHWs in interventions, particularly in diabetes control ( Carrasquillo et al, 2014 ; Castillo at el., 2015 ; Little et al, 2014 ; Rothschild et al, 2013 ), cardiovascular disease prevention ( Balcazar et al, 2014 ; Spinner & Alvarado, 2012 ), and reproductive health ( Lechuga et al, 2015 ). Several studies have used the CHW model to promote physical activity (PA) ( Ayala, 2011 ; Koniak-Griffin et al, 2015 ; Staten et al, 2011 ).…”
mentioning
confidence: 99%